Analyzing and Validating the Competences of the Teachers Profession based on the Model - DARANI, ABBASS BABAEI; DARAEI, MEHRI; FARAHBAKHS, SAEED (The journal of contemporary issues in business and government, 2021)
One of the issues that has been addressed in recent years is the existence of a mechanism for determining and assessing the professional qualifications of teachers who have paid more attention to this in developed countries and have been able to make and develop their own educational system models. To make in our country, this has also been highlighted in recent years, and its underlying work has been somewhat done. In this regard, this research has been conducted with the aim of analyzing and validating the model of professional competencies based on the Huntly model. The statistical population is all teachers working in Isfahan province. Using Cochran's formula, 345 people were selected as a statistical sample and selected randomly. The data gathering tool was a Delphi method and a researcher-made questionnaire. The validity of the questionnaire was content validity and reviewed by five experts and professors. The reliability of the questionnaire was also evaluated using Cronbach's alpha test. The results show that the alpha coefficient is more than 0.7, so the questionnaire has an appropriate reliability. Data analysis was performed using Smart PLS and SPSS20 software. The results show that professional knowledge, professional practice, and professional commitment are highly valued as a component of the professional competences of teachers in Isfahan province.